Mediating Role of Optimism Bias and Risk Perception Between Emotional Intelligence and Decision-Making: A Serial Mediation Model - Chen, Chaoran; Ishfaq, Muhammad; Ashraf, Farzana; Sarfaraz, Ayesha; Wang, Kan (Frontiers in Psychology, 2022)
The commodity market plays a vital role in boosting the economy. Investors make decisions based on market knowledge and ignore cognitive biases. These cognitive biases or judgment errors have a significant effect on investment decisions. Therefore, the study aims to investigate the effect of emotional intelligence on decision-making. In addition, optimism bias and risk perception are the intervening variables between the emotional intelligence and decision making. So this study contributed to the body of knowledge by examining the mediating role of optimism bias and risk perception. The data is collected from the respondents of the commodity market and the 370 questionnaires are distributed to investors. Out of which, 337 respondents give their feedback. The convenience base sampling technique is used due to the easy access of respondents, time and cost factors. Data is entered into the SPSS 26 and process macro model 6, proposed by Hayes (2017) is used for the serial mediation. Results of this study is aligned with the literature that there is a significant effect of emotional intelligence on decision-making. It is also analyzed that optimism bias has a positive effect on decision-making. The finding of this study will be helpful for the brokers, the government and especially the investors. This study also proposed that future studies can be conducted on the stock exchange and real estate market comparative analysis.